GENERATION GAP CONFLICT AND ITS IMPACT ON EMPLOYEE PERFORMANCE - Lina Dameria Siregar; F.X. Parama Santati; Nia Meitisari (SEAN Institute, 2023)
The purpose of this study is to demonstrate and explain the influence of the generation gap conflict between millennials and older employees on employee performance. The meeting of three or even four generations in one organization currently marks the generation gap. These distinctions cause generational conflicts. Long-term conflict will undoubtedly have an influence on performance. This study's demographic is people of working age with years of birth, specifically the baby boomers generation (1946-1964), generation X (1965-1980), generation Y or millennials (1981-1996), and generation Z (1997-2012), with up to 200 respondents. This study collected primary data via distributing questionnaires. Descriptive analytic techniques and multiple linear regression analysis were used to handle and analyze the data. According to the findings of this study, communication, opinions on work values or ethics, perspectives on rules and authority/hierarchy, and knowledge of technology all have an impact on employee performance.